Os litores da nossa burguesia: o Mídia sem Máscara em atuação partidária (2002-2011) - Patschiki, Lucas (2012)
In this dissertation we investigated the performance of the partisan group organized around the website Maskless Media (Mídia Sem Máscara, www.midiasemmascara.org) between the years 2002 and 2011. The website was founded in the year of 2002 in the context of presidential elections to elect Luiz Inácio Lula da Silva of the Workers Party (Partido dos Trabalhadores), presenting itself as an observatory of the press, under the responsibility of the main organizer Olavo de Carvalho. He proposed through the Mídia Sem Máscara group a series of right-wing intellectuals around an ideological component: the anticommunism. After this election there is a fast rise on anticommunism in Brazilian media as an element of pressure on the Labor Party to fulfill the commitments made with the bourgeoisie and imperialism. Explanation that is not sufficient to characterize the progress of an organized movement of fascist type, which we´ll analyze through the limits of ultra-liberalism as a social-historical project, unable to resolve the crisis of capital-imperialism. In this conjuncture its anticommunism served as common ideological basis for the fascist spectrum of society, organizing a movement aiming the intensification of class struggle. Starting from this bases, the group Mídia sem Máscara began their militating for a fascist project - not yet fully developed, given the circumstances. Fascism is here understood as a phenomenon born with imperialism, which first political and social function is to rearrange the block in the power in a brutal manner during the open crisis, for the maintenance and reproduction of class society which indicates its character of constant struggle against the working class and generally against any democratic advance. This does not mean that any crisis gives way to an alternative fascist, but is by the perspective of institutional breakdown that contemporary fascist movements are organized. It is one of the prerogatives of what we might call the third fascist wave , ideologically distinct from the previous by the acceptance of the ultra-liberal economic presuppositions and organizationally by the emphasis on the formation of networks around the party. We investigate in this dissertation: the approaches to the immediate history in academy; the production of historical knowledge and the question of historical truth; the qualitative developments of capitalism in the last century; the development of the internet as part of the expansion of forms of reproduction of capital; the installation of Internet in Brazil; fascist movements in its transformations; the public career of Olavo de Carvalho; the formation of the Mídia Sem Máscara and its affirmation; its organization; discursive peculiarity; ways of activity for propaganda, cooptation and training of their readers-militants over the internet; the social groups which are aimed; its network around the party; and their ideological assumptions, emphasizing the specificity of their anticommunism (the anticommunism against Gramsci).